Encapsulation of Lactobacillus plantarum with Mannan and Sodium Alginate Improves its Cell Production (Journal of Biochemistry, Microbiology and Biotechnology, 2019)
Probiotic bacteria are utilized in aquaculture as they exert a crucial function in promoting and maintaining the fish health. Probiotic strains should be present in a viable form during consumption and throughout the gastrointestinal tract for maximum health benefits. Many reports stated that there is poor survival of probiotic in products containing free probiotic cells. Providing probiotic living cells with physical barrier to resist adverse environmental conditions is therefore an approach currently receiving considerable interest. In this study, Lactobacillus plantarum was encapsulated with mannan and sodium alginate to increase probiotic viability. Response surface methodology (RSM) based on Box-Behnken design was used to optimize the encapsulation process with mannan concentration (5 to 30 % w/v) and sodium alginate concentration (1 to 5 % w/v) as the independent variables evaluated. According to the regression coefficients and significance of the polynomial model, the optimum encapsulation parameters were as follows: 24.73 % w/v mannan; 1.6 % w/v sodium alginate. Under these conditions of encapsulation, the total cell production of the Lactobacillus plantarum was increased to 5.3 (108 CFU/g) as compared to the free cell culture, 3.2 (108 CFU/g).
Keywords: Encapsulation; Lactobacillus plantarum; mannan; oligosaccharides; Response Surface Methodology